If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 1) = 2x + 56 Reorder the terms: 7(1 + x) = 2x + 56 (1 * 7 + x * 7) = 2x + 56 (7 + 7x) = 2x + 56 Reorder the terms: 7 + 7x = 56 + 2x Solving 7 + 7x = 56 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 7x + -2x = 56 + 2x + -2x Combine like terms: 7x + -2x = 5x 7 + 5x = 56 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + 5x = 56 + 0 7 + 5x = 56 Add '-7' to each side of the equation. 7 + -7 + 5x = 56 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 56 + -7 5x = 56 + -7 Combine like terms: 56 + -7 = 49 5x = 49 Divide each side by '5'. x = 9.8 Simplifying x = 9.8
| 4x+12=-3-2x | | 5y+2y-4=9 | | 5M-6=17 | | 8x-4+2x+6-2x=34 | | 0.33x+0.33(2x-15)=3.50 | | (h-10)/3=-4 | | 3(3x+14)=12x | | -3x-7=x+9 | | 2(4y+1)=-3(5+y) | | 526.24=170+1.22x | | 9d+4d+d+9=2d | | 5w+5=16 | | 16x^2+8x+6=0 | | y=(x*x)+2 | | x+x/2+x/4=1 | | A=bxh | | 5.8-0.1x=0.2x-0.2 | | 10+(2x+1)^2/3=13 | | 9-4s+3+5s+6s=33 | | 90=39.58+0.25x | | 7(x-7)=3 | | 2p-1600=-4x | | 3x-2(x+7)=-10 | | 1/3(c-18)=7 | | 15y-8y=21 | | 96=8(x+4) | | -2(1+5a)=-6(a+3) | | 5c-3+2c-c=15 | | 5(8+2c)=3(3c-5) | | 4b-3c=d | | 5g-7=58 | | -196=7(4r-5)+7 |